The Influence of Product, Price, and Location on Consumer Purchasing Interest in Bakso Pak Kus Residen Sudirman Surabaya - Dimas Septian Wijiantoro (NAROTAMA UNIVERSITY, Indonesia, 2019)
Companies need to maintain their survival by developing and earning profits. Consumers have ever-changing tastes and desires, so companies must be prepared to face all these changes and constantly review and improve their offerings. Companies need to pay attention to factors that affect consumers' buying interest, including products, prices, and locations. This study aims to determine and analyze the effect of simultaneous product, price, and location on consumer buying interest in Bakso Pak Kus Jalan Sudirman Residen Surabaya. The study population was all consumers of Bakso Pak Kus Jalan Sudirman Resident Surabaya. The sampling technique is based on Hair, et al. (2010), that the number of samples is at least 5 times the number of indicators so that the number of samples in this study is 85 people. The data analysis technique used multiple linear regression, t test, and F test. The results showed that the product, price, and location partially affected the consumer buying interest of Bakso Pak Kus Jalan Sudirman Resident Surabaya as evidenced by the results of the t test showing the calculated t value all independent variables are greater than t table (1,989), which is 2,015 for the effect of product variables (X1), 2,608 for the influence of price variables (X2), and 6,037 for the effect of location variables (X3). . The results also show that the products, prices, and locations simultaneously influence consumers' buying interest in Bakso Pak Kus Jalan Sudirman Resident Surabaya as evidenced by the results of the F test which shows the value of F count> F table which is 45,001> 2,716.